Explainable machine learning for the early differentiation of pediatric bronchopneumonia using routine laboratory parameters - Jinxing Dai; Hao Qiu; Liran Shen; Qianjin Shi; Kang Shen; Qingkai Wang; Weibing Qiu (PLoS ONE, 2026)
Objective Early differentiation of pediatric acute respiratory infections in outpatient and emergency settings is often hindered by nonspecific clinical signs, leading to unnecessary empirical antibiotic use and avoidable radiation exposure. Therefore, this study aimed to develop and internally evaluate an early triage model to distinguish pediatric bronchopneumonia (BP) from uncomplicated upper respiratory tract infection using routine, cost-effective laboratory parameters analyzed with machine-learning algorithms. Methods This retrospective study consecutively enrolled 532 pediatric patients who presented with mild respiratory symptoms at their initial visit, comprising 218 in the BP group and 314 in the Upper Respiratory Tract Infection (URTI) group. Core laboratory indicators were selected using a dual-dimensionality reduction strategy that integrated the Least Absolute Shrinkage and Selection Operator (LASSO) regression with the Boruta algorithm. Seven machine learning classifiers were then constructed and compared based on the resulting feature matrix. The Shapley Additive Explanations (SHAP) framework was subsequently applied to interpret the nonlinear predictive mechanisms of the optimal model. Results This study constructed seven machine learning models: Logistic Regression (LR), Decision Tree (DT), Random Forest (RF), Extreme Gradient Boosting (XGBoost), Lightweight Gradient Boosting Machine (LightGBM), Support Vector Machine (SVM), and Artificial Neural Network (ANN). In the internal validation set, the SVM model demonstrated favorable predictive performance, with an area under the curve (AUC) of 0.921 (95% confidence interval: 0.874–0.959). Based on Platt-scaled probability estimates, the SVM model showed the lowest Brier score among the evaluated models, with a Brier score of 0.112. Decision curve analysis confirmed this model’s positive net clinical benefit across a broad range of threshold probabilities. SHAP analysis further elucidated the nonlinear contribution weights of multiple conventional parameters at specific physiological thresholds. Conclusions The multidimensional SVM risk quantification model, based on nine routine laboratory parameters, provides an accurate and objective assessment of pediatric BP risk. This model holds significant potential for clinical translation as a noninvasive, cost-effective triage tool in emergency departments. Its application could effectively reduce unnecessary radiographic screening and excessive antibiotic use.